Overcoming Speaking Anxiety: A Study on Students’ Preferred Strategies in English Language Learning - Herlina, Herlina; Aridah, Aridah; Hermagustiana, Istanti; Sunggingwati, Dyah; Syamdianita, Syamdianita (Journal of Language and Literature Studies, 2026)
Speaking anxiety is a major challenge for students learning English as a foreign language. It often arises from fear of making mistakes, limited vocabulary, poor pronunciation, and the pressure of being judged. This study explores how English Education students at Mulawarman University experience and manage speaking anxiety. Using a qualitative design with semi-structured interviews involving three participants, data were analyzed thematically to identify patterns in causes, triggers, and coping strategies. The findings reveal that anxiety is most intense during formal tasks such as presentations or spontaneous questioning. Students adopt strategies like self-practice, note preparation, breathing techniques, self-recording, and peer support to reduce anxiety. These approaches gradually enhance confidence and improve speaking performance. The study concludes that emotional and instructional support from teachers and peers significantly reduces anxiety levels. Implications suggest that educators should foster supportive classroom environments and integrate reflective speaking practices to help students overcome fear and participate actively in English communication.